Do Malaysia and Pakistan are suitable for a comparative study of SMEs: an intellectual capital perspective? - Muhd Sadique, M. K. (Interdisciplinary Journal of Contemporary Research, 2011)
Intellectual capital appears as the most important and vital component of a knowledge-based economy. Present economy is known as a knowledge-based economy where, knowledge, information and soft assets have more importance rather than the physical assets. The role and importance of SMEs in a knowledge-based economy has been highly appreciated and acknowledged. Moreover, in the present economy, SMEs are facing tremendous challenges and threats to survive in a competitive environment. In a competitive environment the hightech SMEs need to upgrade their intellectual capital including knowledge, database, technological advancement and innovation in order to stay in a competitive environment. Therefore, SMEs need to focus on the exploitation and application of their intellectual capital.